The Using Of Linking Words to Enhance Students’ Writing Ability at Universitas Potensi Utama - Reni Rosianna Lumbangaol (Journal MELT (Medium for English Language Teaching), 2022)
Nowadays, there has been great attention to studying the students writing ability as Foreign Language learners, especially the essay writing skills of non-native speaker students. The purpose of this study is to analyze the types of errors in using the linking words and phrases. The writer is focused in analyzing student examination results in essays term at medium-level academic writing course and state the main causes of these errors. The research method is a classroom research study. This research is based on Ngadda and Nwoke’s (2014) theories on the classification of errors and Biber et al.’s (2002) classification of linking adverbials as well as presents the frequency of the types of errors. The research object is students of Potensi Utama University at English Education program students in the fifth semester of the 2021-2022 Academic Year. The main findings of the research indicate that linking words were seldom applied in writing because students' comprehension was very low. The teaching and learning process in exploring linking words certainly raised the level of students in mastering linking words in writing. The research consisted of 32 English students at Potensi Utama University. They were tested to know their writing ability in the capability of using linking words. The results indicated that there was a significant improvement in students’ writing ability after learning to link words comprehensively. The students were able to use and place the linking words correctly.  The writer found that the students were able to manage linking words at Pre-Test was 9,38% and raise to 90,63% at Post-Test. Certainly, it is important to master the linking words to improve students’ ability in writing skills.